Three new ostracod species from coastal Australian waters (Crustacea: Ostracoda: Myodocopa: Cylindroleberididae) - Syme, Anna E.; Poore, Gary C.b. (Zootaxa, 2006)
Three new species of Cylindroleberididae are described: Parasterope gamurru from Lizard Island (Queensland), Diasterope wirraka from Bass Strait (Victoria), and Cylindroleberis marranyin from Sandy Point (Victoria). This is the first record of species of Cylindroleberis and Diasterope from Australia, and the first record of a species of Parasterope from Queensland. Juvenile instars of species of Cylindroleberis are compared in order to assign appropriate stages to those of Cylindroleberis marranyin.